Factors Associated with Home Delivery in West Pokot County of Kenya - Jared Otieno Ogolla (Hindawi Limited, 2015)
Background. This paper sought to estimate the percentage of women who deliver at home in West Pokot County and establish the factors associated with home delivery in the area. Design and Methods. The cross-sectional survey targeted 18,174 households between the months of April and July 2013. Six hundred mothers participated in the study. Association between predictors and the place where the delivery took place was analysed by chi-square test (χ2) at 95% confidence interval. Factors with P value < 0.05 were considered statistically significant. These factors were entered into multivariate logistic regression model after controlling for confounding to ascertain how each one influenced home delivery. Odds ratio was used to determine the extent of association. Results. Based on the mother's most recent births, 200 (33.3%) women delivered in a health facility while 400 (66.7%) delivered at home. Factors associated with home delivering were housewives (OR: 4.5, 95% CI: 2.1-9.5; P=0.001) and low socioeconomic status of 10 km (OR: 0.5, 9.5% CI: 0.3-0.7; P=0.001). Conclusions. The findings of this study provide novel information for stakeholders responsible for maternal and child health in West Pokot County.